Subcutaneous Immunization of Dogs With Bordetella bronchiseptica Bacterial Ghost Vaccine - Muhammad, Abbas; Kassmannhuber, Johannes; Rauscher, Mascha; Falcon, Alaric A.; Wheeler, David W.; Zhang, Alan A.; Lubitz, Petra; Lubitz, Werner (Frontiers in Immunology, 2019)
The Bordetella species are Gram-negative bacterial pathogens that colonizes mammalian respiratory tract causing respiratory diseases in humans and animals. Bordetella bronchiseptica causes clinical conditions in many mammals including immunocompromised humans. Using the dog model of respiratory infection it has been shown in this study that newly developed Bordetella bronchiseptica Bacterial Ghost (BbBG) vaccine exhibited significant protection in the face of a severe pathogenic bacterial challenge in seronegative dogs. The protein E-specific lysis mechanism was used to produce BbBGs. Bacterial Ghosts (BGs) are empty cell envelope of Gram-negative bacterium which are genetically processed to form a microscopic hole in their membrane, through which all the cytoplasmic contents are expelled leaving behind intact empty bacterial shells. BGs due to their intact surface structure offers the safety of inactivated but efficacy of live attenuated vaccines. In this study, seronegative dogs were vaccinated subcutaneously (s/c) with two different doses of newly developed BbBG vaccine (lower 10^5 (BbBG – 5) and higher 10^7 (BbBG – 7)) on day 0 and 21. The animals were challenged (by aerosol) with virulent live B. bronchiseptica strains 41 days after first vaccination. The dogs vaccinated s/c with BbBG – 7 vaccine had significantly lower spontaneous coughing scores (P = 0.0001) than dogs in negative control group. Further, the tested BbBG – 7 vaccine was equivalent to the positive control vaccine Bronchicine CAe in terms of safety and efficacy. For the first time here in this study we report the successful use of liquid formulated BGs vaccines in animal studies. Earlier reported studies using BGs vaccines were performed with resuspended freeze-dried BGs preparations.